INTERPRETASI TEORI DELEUZE DAN GUATTARI DALAM ARSITEKTUR - Solaiman Bakir; Melania L. Pandiangan; Genie Anggita; Rangga Alexander (ATRIUM: Jurnal Arsitektur, 2015)
Title: Interpretation of Deleuze and Guattari Theories in Architecture Philosophy influenced all architects through theories of philosophy which is it acted as a set of the idea to practice in design. It is can be looked at the contemporary architectural trend which trying to demonstrated the deconstruction philosophy through architecture style, or it is can be observed in architecture literature which trying to adopt the philosophy of phenomenology and so forth. These examples revealed that there are relationship between philosophy and architecture. So, In this case, the philosophy become very important and then to be an alternative in term of exploration and searching the new concepts of creation of architecture. Both of Gilles Deleuze and Felix Guatari are thinkers or philosophers that revolutionary. Their thought influenced architecture although not so much whom that directly apply their work. In this paper, we try to interprete their toughts which covered Desire-Machine Concept, Territorialization- Deterritorializatiion-Reterritorialization Concept, and Rhizome-Tree Concept as well as its application in the field of architecture. It can be an image or an idea of design.